Effect of wearable fitness technology trust on sports injury prevention awareness and cross-sport athletic performance in pentathletes - Ali, Y.; Umair, M.; Mahmood, A.; Noor, A. (14th International Scientific Conference "Science and Higher Education in Function of Sustainable Development", 2025)
Currently, the use of wearable technology during sporting events is less researched among Asian sporting federations compared to those in Europe. Pedagogical engineering explored in the context of sports and physical education 4.0 is integral. This paper examines wearable fitness technology and its impact on sports injury prevention awareness and cross-sport athletic performance in pentathletes. The study is a correlational cross-sectional quantitative research project. Data collection occurred from December 2024 to February 2025, involving 220 athletes participating in pentathlon sports: laser running, swimming, fencing, obstacle running, and jumping. This includes athletes who utilise Garmin technology. Descriptive and inferential statistics were analysed using IBM SPSS version 28. After performing normality tests using Log10 and SQRT commands, parametric tests were conducted. A significant Pearson correlation was found among the three constructs studied. Regression analysis revealed that wearing fitness technology significantly influences sports injury prevention awareness and cross-athletic performance in pentathlon sports. Furthermore, multivariate analysis of variance indicated that both sporting experience and income had significant main effects on the three constructs examined. Independent sample t-tests demonstrated that male pentathletes had greater trust in wearable fitness technology, along with higher sports injury prevention awareness and improved athletic performance, compared to their female counterparts. The study is integral in the field of academia-industry partnerships, mobile learning applications and social aspects of digitalization.